2018
DOI: 10.1186/s12889-018-5421-x
|View full text |Cite
|
Sign up to set email alerts
|

“People look and ask lots of questions”: caregivers’ perceptions of healthcare provision and support for children born with cleft lip and palate

Abstract: BackgroundClefting of the lip and/or palate (CL/P) is amongst the five most common birth defects reported in South Africa. The emotional impact on parents at the birth of their new-born with CL/P could affect parent-child relationships. In light of insufficient scholarly attention parental experiences and perceptions, this study reports on caregivers’ perceptions of health service provision and support for children born with cleft lip and palate in South Africa.MethodsThe study setting consisted of 11 academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 47 publications
1
39
0
4
Order By: Relevance
“…A study pointed out the need to support families of children with cleft lip and palate beyond the support from the health system, which should provide quality care, including guidance and training to parents and caregivers. The study also pointed out the need for education and training of health professionals outside specialized centers, for public awareness-raising activities on birth defects and for social support programs (21) .…”
Section: Discussionmentioning
confidence: 97%
“…A study pointed out the need to support families of children with cleft lip and palate beyond the support from the health system, which should provide quality care, including guidance and training to parents and caregivers. The study also pointed out the need for education and training of health professionals outside specialized centers, for public awareness-raising activities on birth defects and for social support programs (21) .…”
Section: Discussionmentioning
confidence: 97%
“…Notwithstanding the controversies regarding the use of feeding plates, [45][46][47] feeding difficulties following the birth of babies with CLP are common and the feeding plate can assist with closure of the cleft to facilitate sucking and to prevent choking. A study among caregivers of CLP children found that feeding difficulties were one of the most distressing aspects in caring for the children, [48] highlighting the importance of adequate support and assistance to caregivers regarding feeding methods.…”
Section: Researchmentioning
confidence: 99%
“…This will assist with the reduction of possible physical impairment and societal courtesy stigma and discrimination. [48,52] There was variation in the number of team members at CLP centres, ranging from 2 to 8. In most centres, there was a scarcity of certain specialists.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with NSCL/P are also associated with an increased risk of cancers [ 2 ] and an elevated overall mortality into adulthood [ 3 ]. NSCL/P increases economic and psychosocial burdens on the subjects, their families, and the society [ 4 ].…”
Section: Introductionmentioning
confidence: 99%